The role of higher education institutions in the accessible tourism ecosystem: requirements for the conceptualization of an information system - Teixeira, Pedro (2022)
For information systems to be successful, it is important to involve and consider the perspective of all stakeholders. In the accessible tourism market, higher education institutions (HEI) are a very important stakeholder, playing a major role in training and research. This work intends to explore the information requirements that are most valued by higher education institutions in order to conceptualize a Web-based information system which is capable of promoting more accessible tourism conditions for visitors with disabilities (VwD). To achieving this goal, questionnaires were applied to a sample of students and directors of tourism in HEI. Generally speaking, both groups understood the need for a Web platform and also revealed interest in using it. Regarding information to retrieve from the platform, accessible market characteristics and training opportunities were highlighted, while inputs connected to research sharing were the best regarded. Overall, this work allows a general view of information technologies in education, for the specific case of accessible tourism.